Kajian Fitokimia dan Potensi Bioaktif Sayur Kelakai (Stenochlaena palustris) sebagai Sumber Serat dan Zat Besi untuk Kesehatan - Leviona Dhina Safira; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Kelakai vegetable (Stenochlaena palustris) is a fern plant commonly consumed by communities living in wetland and swamp areas, particularly in Kalimantan. Traditionally, this plant has been used as a daily vegetable and is believed to provide health benefits, especially in improving blood quality and maintaining physical vitality. This study aims to review, based on literature sources, the phytochemical content and bioactive potential of kelakai as a source of dietary fiber and iron for health promotion. Various literature sources indicate that kelakai contains diverse phytochemical compounds, including flavonoids, phenolic compounds, alkaloids, and tannins, which exhibit potential antioxidant activity. The dietary fiber content in kelakai plays an important role in supporting digestive health, assisting in blood glucose regulation, and maintaining gut microbiota balance. In addition, kelakai is reported to have relatively high iron content compared to several other green vegetables, suggesting its potential role in preventing anemia, particularly iron deficiency anemia. The bioactive properties of kelakai also contribute to cellular protection against oxidative stress and support metabolic functions in the body. Based on this literature review, kelakai demonstrates significant potential as a local functional food with valuable nutritional and health benefits. Further development and utilization of kelakai are expected to support food diversification and contribute to improved public health outcomes